(untitled) (SAARC Journal of Agriculture, 2026)
Seed sovereignty has emerged as a critical issue as the expansion of the global intellectual property rights regime is increasingly challenging traditional agricultural practices, farmers’ rights, and biodiversity. This study critically explores the interplay between intellectual property rights and seed sovereignty in the region of South Asia, while focusing upon legal, institutional, and policy frameworks in the countries, while giving a special reference to the Indian legal system in the context. The research highlights how agreements like TRIPS and UPOV intersect with the domestic efforts to protect the rights of farmers and the traditional knowledge. A reference is taken from the law publications, case studies and institutional reports to assess the effectiveness of the regional mechanism and the response of civil society in ensuring that equitable access to seeds is upheld. The community programs and initiatives as Seeds Without Borders, are also examined to understand their potential to resist corporate control on the seeds and to promote regional seed exchange. The research also critically analyses the role of the intellectual property laws in supporting and undermining the idea of seed sovereignty. Overall, the study calls for uniform regional harmonization, farmer-centric approach that aligns with the biodiversity of the region, with a legal mandate to empower farmers to conserve biodiversity and develop agriculture in South Asia. SAARC J. Agric., 23(2): 239-251 (2025)